Одержання неповних естерів ненасичених дикарбонових кислот - Кічура, Дарія; Гладка, Ольга (Видавництво Львівської політехніки, 2012)
The technological aspects of the esterification process ofsaturated and uns aturated anhydrides with on the bases fusel oils С2-С5 alcohols have been thoroughly investigated; the influence of reagents ratio, alcohol nature, nature anhydrides on technological parameters of process have been studied.